2015
DOI: 10.4067/s0718-221x2015005000015
|View full text |Cite
|
Sign up to set email alerts
|

Compression and flexural properties of finger jointed mango wood sections

Abstract: In this paper, an attempt was made to assess the effectiveness of finger jointing in utilising mango wood sections for various end uses like furniture. The study was based on the estimation of Modulus of elasticity and Modulus of rupture under static bending and Maximum Crushing Stress and Modulus of elasticity under compression parallel to grain of finger jointed sections and comparing them with the values measured for clear wood sections from the same lot. For joining the sections, the Poly Vinyl Acetate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
3
3
0
Order By: Relevance
“…Barboutis and Vassiliou (2008) reported MORs of 62-76% upon using 4 different nger pro les and different PVA types for Castanea sativa wood, whereas Kumar et al (2011) obtained MOR of less than 30% for mango wood using PVA adhesive. These appear to corroborate with the conclusion of Frihart (2005) and corroborated by Kumar et al (2015) that rupture and elasticity properties of FJ lumber is less dependent on adhesive used.…”
Section: J Ointefficiencyinm Oeorm or = X100\%supporting
confidence: 89%
See 1 more Smart Citation
“…Barboutis and Vassiliou (2008) reported MORs of 62-76% upon using 4 different nger pro les and different PVA types for Castanea sativa wood, whereas Kumar et al (2011) obtained MOR of less than 30% for mango wood using PVA adhesive. These appear to corroborate with the conclusion of Frihart (2005) and corroborated by Kumar et al (2015) that rupture and elasticity properties of FJ lumber is less dependent on adhesive used.…”
Section: J Ointefficiencyinm Oeorm or = X100\%supporting
confidence: 89%
“…This could mean that, joining stem and branch timber of K. ivorensis could produce better elastic FJ lumber. The trend of increased in exural elasticity of FJ lumber (as exhibited by the group tested at 18 ± 3%mc) is consistent with ndings of Kumar et al (2015) who reported 114.1% with PVA adhesive for FJ mango stemwood and indicated its agreement with Kumar et al (2011) using same adhesive but varied nger pro les. On the other hand, the relatively low MOEs of the sample group tested at 9 ± 3mc also appears to be consistent with Ayarkwa et al (2000) who reported MOEs of FJ lumber of Ghanaian hardwood to be between 83 to 98% of those of unjointed timber upon using resorcinol-formaldehyde adhesive.…”
Section: J Ointefficiencyinm Oeorm or = X100\%supporting
confidence: 89%
“…Both the type of the joint (angle and shape under which the cutting is performed) and the glue type influence the material density, elasticity, and strength. Testing wood joints in bending was previously done and reported in literature, e.g., [11][12][13], but no reference regarding the bending behavior of edge-joints at 45 • was found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Effectiveness of finger jointing in utilizing mango wood sections for various end uses like furniture was evaluated (Kumar et al 2015). It was found that the modulus of elasticity of the sections joined showed significantly better values than that of unjointed clear wood sections.…”
Section: Introductionmentioning
confidence: 99%